A brief review of ergonomic workstation for disability student - Rozimah, Yusof; Nur Haizal, Mat Yaakob @ Ariffin; Ahmad Ikmal Hakim, Ab Ghani (Penerbit UTM Press, 2015)
This paper presents the review of the ergonomic on workstation for disable student in higher education. Most of disable especially in term of physically disable student has limitation in their study area, which highlighted here as workstation. The main objective of this paper is to discuss the significant role of ergonomic workstation for disable students, which will create an enjoyable learning environment for these students thus enhancing their self-motivation to learn. This review was conducted by referring on the published journal articles, conference papers, legislation, standards and other reports available on the internet sources. Data from the literature review shows that the number of disabled persons in Malaysia was on the rise from year 2009 till 2012 and they are facing many challenges in obtaining good education to prepare for their future work life. Many students with disabilities drop-out from high school before graduating, leaving them even more unprepared for and less likely to obtain a job. Therefore, implementation lifelong learning programs could provide them the opportunity to learn and equipped them with the appropriate skills and enhanced their survival in this challenging world.